IMPROVEMENT OF THE COSTS AND CONTROL OVER FINANCIAL RESOURCES OF HIGHER EDUCATIONAL INSTITUTIONS (American Journal of Interdisciplinary Research and Development, 2025)
This article covers the issues of planning and improving the mechanisms of control over the financial resources and costs of higher education institutions. State and non-state sources of financing of the educational system, methods of budgeting based on productivity and their impact on the activities of educational institutions have been analyzed. Also, important aspects of improving the efficiency of expenses, rational use of financial resources and ensuring the financial independence of higher education institutions are revealed. The article developed recommendations for qualitative changes in funding in education based on an analysis of national and international experiences.